The Structures of the Film Experience by Jean-Pierre Meunier Historical Assessments and Phenomenological Expansions - Hanich, Julian; Fairfax, Daniel (Film Theory in Media History, 2019)
For the first time this volume makes Jean-Pierre Meunier’s insightful thoughts on the film experience available for an English-speaking readership. Introduced and commented by specialists in film studies and philosophy, Meunier’s intricate phenomenological descriptions of the spectator’s engagement with fiction films, documentaries and home movies can reach the wide audience they have deserved ever since their publication in French in 1969.